2012
DOI: 10.3390/app2030566
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Morphological Parameters of Supported Gold Nanoparticles: Comparison of AFM Combined with Optical Spectroscopy and Theoretical Modeling versus TEM

Abstract: The morphology of small gold particles prepared by Volmer-Weber growth on sapphire substrates have been investigated by two different characterization techniques. First, by non-extensive atomic force microscopy (AFM) in combination with optical spectroscopy and modeling of the optical properties using a theoretical model, recently developed in our group. Second, by extensive transmission electron microscopy (TEM). Comparing the results obtained with both techniques demonstrate that for small gold nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…(2) suitability for characterizing low-density nanomaterials, offering better contrast. (3) providing 3D images and enabling measurement of the NP height, and (4) costing much less and occupying a smaller laboratory space. In 2017, Al-Anssari et al used AFM to confirm NP adsorption on the calcite surface. They observed that nanofluid-treated calcite exhibited higher surface roughness, with roughness values increasing from 18–32 nm on the original calcite surface to 450–580 nm when treated at room temperature and up to 2100–2700 nm when treated at higher temperatures (60 °C) …”
Section: Instrumental Measurements Applied In Nanoeormentioning
confidence: 99%
“…(2) suitability for characterizing low-density nanomaterials, offering better contrast. (3) providing 3D images and enabling measurement of the NP height, and (4) costing much less and occupying a smaller laboratory space. In 2017, Al-Anssari et al used AFM to confirm NP adsorption on the calcite surface. They observed that nanofluid-treated calcite exhibited higher surface roughness, with roughness values increasing from 18–32 nm on the original calcite surface to 450–580 nm when treated at room temperature and up to 2100–2700 nm when treated at higher temperatures (60 °C) …”
Section: Instrumental Measurements Applied In Nanoeormentioning
confidence: 99%
“…The TEM images only reveal the lateral dimension of the nanoparticle but no information on the nanoparticle height. Though, with the dimension of the width particles from the TEM images, the lateral particle size distribution can be obtained [22]. From the histogram, the size distribution is narrow, and the major peak is centered at 480, 410, and 230 nm.…”
Section: Parameters Optimizationmentioning
confidence: 99%